Synthesis, characterization, and biological activity of Cu(II) and Co(II) complexes of novel N1, N2-bis(4-methyl quinolin-2-yl)benzene-1, 2-diamine: CuO and CoO nanoparticles derived from their metal complexes for photocatalytic activity. Issue 8 (3rd August 2021) - Venugopal, N.; Krishnamurthy, G.; Bhojyanaik, H. S.; Madhukar Naik, M.; Sunilkumar, N.
Abstract: The present work focuses on the synthesis of Cu(II) and Co(II) complexes obtained from 2-Chloro-4-methylquinoline and o -Phenylenediamine. The newly obtained compounds were characterized by elemental analysis, UV–Vis, FTIR, 1 H NMR, LC–MS, and magnetic susceptibility measurement. The molar conductance values indicate the non-electrolytic nature of the complexes. Based on spectral data indicate octahedral geometry for both Cu (II) and Co(II) complexes. The metal complexes were used as precursors for the synthesis of CuO and CoO nanoparticles via solid-state thermal decomposition without using a catalyst and both the synthesized metal oxide was showed good photocatalytic activity for the degradation of methylene blue dye. Furthermore, the synthesized ligand and its metal complexes have been tested for antibacterial and antifungal activity. The metal complex showed enhanced antitubercular activity against M. tuberculosis. The in-silico molecular docking study was used to predict the binding interaction of the prepared compounds with target receptor GlcN-6-P synthase.